EXPLORING THE IMPACT OF CORPORATE SOCIAL RESPONSIBILITY, GOOD CORPORATE GOVERNANCE AND ENVIRONMENTAL PERFORMANCE ON RETURN ON ASSETS - Kusuma Dewi, Yonanda Roro; Tubastuvi, Naelati; Purwidianti, Wida; Widyaningtyas, Dian (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2025)
This research aimed to assess the impact of Corporate Social Responsibility (CSR), Board of Directors, Independent Commissioner, Institutional Ownership, and Environmental Performance on Financial Performance. The population in this analysis consisted of 129 Consumer Non-cyclical sector firms listed on the Indonesian Stock Exchange from 2020 to 2023. Using purposive sampling, a sample of 45 firms with 102 observations was generated. The data was analyzed quantitatively and processed using the SPSS program. The findings of this research show that Corporate Social Responsibility negatively impacts Financial Performance and Independent Commissioners positively and significantly affect Financial Performance. Then, the Board of Directors, Institutional Ownership, and Environmental Performance do not affect financial performance. This research implies that Consumer Non-cyclical sector firms can increase the ratio of independent commissioners to enhance their financial performance, and these firms need to revisit their CSR approach to ensure it contributes more effectively to financial performance.